Assessment of Geodetic Methods in Investment and Rehabilitation of Bridge Cranes - أحمد, محسن; فحصه, اياد; غصه, حسين (Latakia University Journal -Engineering Sciences Series, 2020)
The research includes a study that helps in monitoring the work of bridge cranes with huge loads and weights and how to rehabilitate those outside the service according to several geodetic methods and according to the devices available in the labor market so that they achieve the requirements of accuracy, ease and safety during use. Initially, the types of gantry cranes used in mega-factories, the geodetic methods used in their construction, and the conditions that the axis have to be fulfilled. The geodetic methods used to monitor the gantry rails axis are presented, field measurements are presented, and the practical comparison is between methods.